Transendoscopic Ventriculocordectomy Using Monopolar Electrosurgical Instrumentation for Conjunctive Treatment of Laryngeal Hemiplegia in Horses: 24 Cases (2017–2019) - Caspers, McKenna K.; Bell, Chris D.; Tatarniuk, Dane M. (Frontiers in Veterinary Science, 2021)
Objective: The objective of this study is to evaluate the safety, efficacy, and owner satisfaction following electrosurgical ventriculocordectomy (EVC), in conjunction with prosthetic laryngoplasty, in equine clinical cases affected with left or right-sided recurrent laryngeal neuropathy. Methods: Retrospective data analysis of clinical signalment, surgery, athletic outcome, intra- and post-operative complications and post-operative examinations from clinical cases wherein EVC was performed in conjunction with traditional prosthetic laryngoplasty from one practice. Owners were contacted by phone or email for a follow up questionnaire. Results: Twenty-four horses underwent unilateral EVC, performed transendoscopically under sedated restraint, using monopolar electrosurgical instrumentation successfully. One horse experienced excessive intraoperative hemorrhage. No horses demonstrated post-operative complications. Twenty (20) cases had a history of increased airway noise prior to surgery. In fifteen of these cases (15/20, 75%) the airway noise was reported as fully improved post-surgery. Eighteen (18) cases had a history of exercise intolerance prior to surgery. In fifteen of these cases (15/18; 83%) the exercise intolerance was reported as resolved. Conclusion: EVC, in conjunction with prosthetic laryngoplasty, can contribute to improvement of RLN symptoms and aid in the effective return to athletic work. Performing transendoscopic ventriculocordectomy with monopolar electrosurgical instrumentation provides comparable clinical outcomes to traditional techniques using a diode-laser or direct excision via laryngotomy.